2019
DOI: 10.1097/pec.0000000000000936
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Tools for Educating Caregivers About Childhood Fever

Abstract: Web-based interventions are associated with significant improvements in caregiver knowledge about fever and high caregiver satisfaction. These interventions should be used to educate caregivers pending the demonstration of improved patient-centered outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
8
0
1
Order By: Relevance
“…This makes it difficult to draw conclusions about the absolute benefit of providing any form of discharge instructions (video or paper). Although not specific to AOM, video discharge instructions provided to parents in the ED setting have consistently been associated with improved knowledge . In contrast, much fewer studies have explored the effectiveness of video discharge instructions on disease‐specific health outcomes and compliance .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This makes it difficult to draw conclusions about the absolute benefit of providing any form of discharge instructions (video or paper). Although not specific to AOM, video discharge instructions provided to parents in the ED setting have consistently been associated with improved knowledge . In contrast, much fewer studies have explored the effectiveness of video discharge instructions on disease‐specific health outcomes and compliance .…”
Section: Discussionmentioning
confidence: 99%
“…Assuming a standard deviation (SD) of 3.43, a type I error rate of 5% and 90% power, 60 individuals/group were required. Based on previous work requiring a 72‐hour follow‐up, the sample size was increased by 65% for loss to follow‐up and 10% for dropouts, giving a rounded sample size of 105 individuals per group. All data were recorded using the Research Electronic Data Capture (REDCap) platform and analyzed using SPSS (version 24, IBM SPSS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal is to ensure that the KT tools promote enhanced knowledge adoption and are user-friendly by involving parents in their development and evaluation (i.e., through patient engagement strategies). Recently, literature has suggested that KT tools developed in a web-based format are associated with better caregiver knowledge uptake compared to traditional methods, such as pamphlets or verbal advice [16].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Video discharge instructions have been shown to be preferred over paper instructions in many pediatric presentations; however, no study has explored the effectiveness of video instructions for AOM. 14,15…”
Section: Introductionmentioning
confidence: 99%